Traditional ecological knowledge in restoration ecology: a call to listen deeply, to engage with, and respect Indigenous voices. Issue 4 (5th May 2021) - Robinson, Jake M.; Gellie, Nick; MacCarthy, Danielle; Mills, Jacob G.; O'Donnell, Kim; Redvers, Nicole
Abstract : The United Nations heralded 2021–2030 as the UN Decade on Ecosystem Restoration. A socioecological approach to restoration has been proposed that honors the diversity in ecological landscapes and their respective cultures and peoples with the goal of repairing degraded ecosystems. Indigenous peoples are intimately interconnected with landscapes, which are under mounting pressure from anthropogenic global environmental change. Article 31 of the UN Declaration on the Rights of Indigenous Peoples states the rights of Indigenous peoples to maintain, protect, and control their culture and traditional ecological knowledge (TEK); however, these rights have not always been acknowledged. We are concerned that large global restoration goals will continue to promote TEK extraction that further perpetuates inequities and discrimination of Indigenous peoples. If the restoration sector wishes to partner with Indigenous communities leading TEK efforts, it needs to understand established international agreements and proactively protect intellectual property and data sovereignty rights. To illustrate a theme of ethical engagement, we present risks to TEK integrity while highlighting engagement that has successfully promoted Indigenous leadership and self‐determination. We propose that a decade of responsible and respectful restoration will be achieved only with shared principles and an ethical code of conduct for TEK partnerships. We argue that deep listening with Indigenous peoples and engagement with humility and respect needs to be the starting point. Finally, we propose an Indigenous‐led workshop to re‐imagine and re‐develop equitable ways forward for TEK partnerships in restoration, with explicit considerations for the rights, livelihoods, and leadership of Indigenous peoples.